2017
DOI: 10.24171/j.phrp.2017.8.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Sarcopenia in Korean Adults by Age Groups

Abstract: ObjectivesThis study aimed to investigate factors affecting sarcopenia in different age groups among Korean adults aged 20 years or older.MethodsIn this secondary analysis, data were collected from records for 17,968, participants who participated in the Korea National Health and Nutrition Examination Survey during 2008–2011. Data were analyzed using multiple logistic regression to determine the associated factors of sarcopenia by age groups.ResultsThe prevalence of sarcopenia increased significantly with age.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 28 publications
(43 reference statements)
5
54
1
1
Order By: Relevance
“…Four studies included a combined group of hospitalized patients with fractures and community‐dwelling individuals without fractures . Two studies reported retrospective data, 20 studies were cross‐sectional, 13 studies were prospective, and 1 study was a randomized controlled trial examining the effect of nutritional supplementation on bone mineral density and risk of falls . Most of the studies were performed in Europe (12 studies), and Asia (12 studies), followed by Australia (5 studies), South America (4 studies), and North America (3 studies) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four studies included a combined group of hospitalized patients with fractures and community‐dwelling individuals without fractures . Two studies reported retrospective data, 20 studies were cross‐sectional, 13 studies were prospective, and 1 study was a randomized controlled trial examining the effect of nutritional supplementation on bone mineral density and risk of falls . Most of the studies were performed in Europe (12 studies), and Asia (12 studies), followed by Australia (5 studies), South America (4 studies), and North America (3 studies) .…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of sarcopenia varied from 0.3% to 73.0%, depending on the sarcopenia definition applied and the study population. Sarcopenia was diagnosed using one definition or more than one definition . Out of the 36 included studies, EWGSOP (23 studies) was the most commonly used definition, followed by FNIH (7 studies), Baumgartner definition (5 studies), AWGS (4 studies), and IWGS (4 studies) …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations